Rapid mapping of polarization switching through complete information acquisition - Suhas Somnath (Nature Portfolio, 2016)
Resolution of classical piezoresponse force microscopy is limited in data acquisition rates and energy scales. Here, Somnath et al. report an approach for rapid probing of ferroelectric switching using direct strain detection of material response to probe bias, enabling spectroscopic imaging at a rate of 3,504 times faster the current state of the art.